Ultrasound-propelled nanocups for drug delivery - Kwan, J; Myers, R; Coussios, C; al., E (Wiley, 2015)
Ultrasound-induced bubble activity (cavitation) has been recently shown to actively transport and improve the distribution of therapeutic agents in tumors. However, existing cavitation-promoting agents are micron-sized and cannot sustain cavitation activity over prolonged time periods because they are rapidly destroyed upon ultrasound exposure. A novel ultrasound-responsive single-cavity polymeric nanoparticle (nanocup) capable of trapping and stabilizing gas against dissolution in the bloodstream is reported. Upon ultrasound exposure at frequencies and intensities achievable with existing diagnostic and therapeutic systems, nanocups initiate and sustain readily detectable cavitation activity for at least four times longer than existing microbubble constructs in an in vivo tumor model. As a proof-of-concept of their ability to enhance the delivery of unmodified therapeutics, intravenously injected nanocups are also found to improve the distribution of a freely circulating IgG mouse antibody when the tumor is exposed to ultrasound. Quantification of the delivery distance and concentration of both the nanocups and coadministered model therapeutic in an in vitro flow phantom shows that the ultrasound-propelled nanocups travel further than the model therapeutic, which is itself delivered to hundreds of microns from the vessel wall. Thus nanocups offer considerable potential for enhanced drug delivery and treatment monitoring in oncological and other biomedical applications.